Effect of progressive reduction in crude protein and lysine of heavy pigs diets on some technological properties of green hams destined for PDO dry-cured ham production. (November 2016) - Gallo, Luigi; Dalla Bona, Mirco; Carraro, Luca; Cecchinato, Alessio; Carnier, Paolo; Schiavon, Stefano
Abstract: In order to investigate the effects of dietary crude protein (CP) and lysine (Lys) content on some technological properties of green hams destined for Protected Designation of Origin (PDO) dry-cured ham, green hams visual appraisal scores, thickness, iodine number and fatty acid composition of subcutaneous fat, and ham weight losses during seasoning (SL) were assessed. The green hams were obtained from 233 pigs fed four diets containing 140 to 110 g/kg CP and 6.5 to 5.3 g/kg total Lys from 90 to 165 kg body weight. A reduction in dietary CP and Lys of up to 20% compared with conventional feeds led to a 15% increase in the thickness of the subcutaneous fat, a 5% decrease in linoleic and polyunsaturated fatty acids in subcutaneous fat and a 7% decrease in SL. A 20% reduction of CP and Lys in diets for finishing pigs has positive effects on the technological properties of green hams destined for PDO dry-cured ham production.